Perancangan Ontologi Semantik : Representasi Digital Kain Gringsing Bali - Sartana Putra, I Putu Duta Awidya; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023, 2023)
Bali has many cultural heritages that can add to the attractiveness of domestic and international tourists. One of these cultural heritages is the Balinese Gringsing cloth.Gringsing cloth is one of the typical fabrics of Bali and the only cloth made using the double tie technique. It is used in religious ceremonies and wedding ceremonies. Gringsing cloth can be a cultural heritage of the island. Ontology can be transformed into a digital form to preserve this heritage.